Potensi Sumber Karbohidrat Indonesia Sebagai Ingridien Pangan Fungsional dengan Kadar Pati Resisten dan Aktivitas Antioksidan Tinggi - Frendy Afandi (Food Scientia : Journal of Food Science and Technology, 2023)
Determinants of the glycemic index (GI) of carbohydrate food were described in several publications. Important information regarding the physicochemical properties including starch granule diameter, gelatinization temperature, GI value/category, the content of resistant starch, protein, fat, bioactive compounds, amylose, amylopectin and the ratio of amylose and amylopectin have been observed. However, there was a discrepancy among the published data. This study focuses on the resistant starch dan bioactive compound content. Some sources of carbohydrates that have high resistant starch are black rice, aromatic rice, white sorghum, taro, white canna, yam, breadfruit, banana, peas, red kidney bean, jack bean, pigeon pea, and jackfruit seed. Meanwhile, the sources of carbohydrate foods that contain high bioactive compounds are black rice, purple rice, waxy white corn, waxy purple corn, wheat, rye, barley, white sweet potato, red sweet potato, purple sweet potato, taro, arrowroot, white canna, yam, jacatupe, cocoyam, arenga, banana, date fruit, peanut butter fruit, peas, mungbean, pigeon pea, dan tamarind seed. Most of them are indigenous Indonesian carbohydrate foods with the resistant starch content between 10.63%-78.9% (w/w) and antioxidants content ranging from 150-43200 mg/100g on a dry basis. From the forty-nine sources being observed, only eleven sources are not available in Indonesia. Thus, it encourages for consuming various carbohydrate sources which are abundantly available in Indonesia.